Creativity Of English Tutorial Activities In Helping Students Understanding Online Learning In Elementary School - Faizah, Nur; Salsabila, Della Hagian (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Because the covid-19, learning that was originally at school has now become homethrough the online system. Online learning has various limitations, for example, theabsence of gadget facilities (cell phones and laptops), low understanding of digital mediaand limited signal. Students who usually study in class and are explained directly to theteacher, now the teacher only gives reading explanations and gives assignments, thismakes students more confused because there is no clear explanation but are forced tounderstand by doing assignments. This study uses descriptive qualitative research that describes tutoring services in reducing difficulties in student learning during the COVID-19 period. Students always ask to be helped with assignments. Students need assistance in learning, so that the material can be easily understood optimally.